Synthesis of textured 0.8Bi0.5Na0.5TiO3 – 0.2Bi0.5K0.5TiO3 lead-free ceramics - Đại Vương, Lê; Anh Quang, Đào; Anh Tuấn, Đặng; Ngọc Trác, Nguyễn; Khánh Quang, Nguyễn; Thị Thanh Kiều, Võ; Duy Hồng Ngoc, Đào (Hue University Journal of Science: Natural Science, 2019)
In this study, Bi4Ti3O12 templates were synthesized using the molten salt method in Na2CO3 and K2CO3 fluxes. The as-prepared Bi4Ti3O12 templates are composed of plate-like morphologies of lengths 5–20 μm and widths 0.5–1 μm at the heating temperature of 1050 °C. From these Bi4Ti3O12 templates, we studied the synthesis of textured 0.8Bi0.5Na0.5TiO3 – 0.2Bi0.5K0.5TiO3 lead-free ceramics by employing the template grain growth method. The effect of sintering temperature on the structure, microstructure, and degree of orientation of the ceramic materials was investigated. The results show that all the ceramic samples have a pure perovskite phase with a rhombic phase structure in the sintering temperature range from 950 to 1050 °C. At the optimum temperature of 1050 °C, the ceramics exhibit the best physical properties such as density (5.94 g/cm3) (the relative density is 98.84% of the theoretical value). The degree of orientation of the synthesized ceramics has the highest values of 65%.